Coordinate Expansion of Murine Hematopoietic and Mesenchymal Stem Cell Compartments by SHIPi. (17th February 2015) - Brooks, R.; Iyer, S.; Akada, H.; Neelam, S.; Russo, C. M.; Chisholm, J. D.; Kerr, W. G.
Abstract: Promoting the expansion of adult stem cell populations offers the potential to ameliorate radiation or chemotherapy-induced bone marrow failure and allows for expedited recovery for patients undergoing these therapies. Previous genetic studies suggested a pivotal role for SH2 domain-containing inositol-5-phosphatase 1 (SHIP1) in limiting the size of the hematopoietic stem cell (HSC) compartment. The aim of this study was to determine whether our recent development of small molecule SHIP1 inhibitors offers the potential for pharmacological expansion of the HSC compartment in vivo. We show here that treatment of mice with aminosteroid inhibitors of SHIP1 (SHIPi) more than doubles the size of the adult mesenchymal stem cell (MSC) compartment while simultaneously expanding the HSC pool sixfold. Consistent with its ability to target SHIP1 function in vivo, SHIPi also significantly increases plasma granulocyte colony-stimulating factor (G-CSF) levels, a growth factor that supports proliferation of HSC. Here, we show that SHIPi-induced G-CSF production mediates HSC and MSC expansion, as in vivo neutralization of G-CSF abrogates the SHIPi-induced expansion of both the HSC and MSC compartments. Due to its expansionary effect on adult stem cell compartments, SHIPi represents a potential novel strategy to improve declining stem cell function in both therapy induced and genetically derived bone marrow failure syndromes. Stem Cells   2015;33:848–858